Phylogenetic analysis and detection of positive selection in the SIRT gene family across vertebrates - Qiuxi Zhou; Xiongtao Yang; Da Li; Jing Li; Ling Peng; Wenwu He (Scientific Reports)
Abstract SIRT6, a member of the sirtuin protein family, is recognized as a tumor suppressor. This study investigates the evolutionary history of the SIRT gene family and examines the selective pressures shaping their functional divergence. Insights into the evolution of these genes may enhance our understanding of their roles in disease pathology. Seventy-three amino acid sequences and full-length mRNA sequences from 22 vertebrate species and one invertebrate were retrieved from public databases. Phylogenetic relationships among the seven SIRT gene family members were reconstructed using Bayesian inference. Codon-based models were applied to detect site-specific positive selection, and likelihood ratio tests (LRTs) were used to compare model fits. Positively selected sites were identified using Bayesian empirical Bayes (BEB) methods. Phylogenetic analysis revealed that the seven SIRT gene family members in vertebrates originated from gene duplication events. Asymmetric evolutionary rates and natural selection were identified as the primary drivers of SIRT gene divergence. Eleven positively selected sites (23I, 310 S, 311I, 313 A, 316 K, 320 C, 321 A, 322Q, 323 H, 327E, 328P) were identified with high confidence (posterior probability ≥ 99%), suggesting critical roles in functional divergence. The evolution of the SIRT gene family is characterized by gene duplication and natural selection. The reconstructed phylogenetic tree elucidates the relationships among the seven members, with SIRT6 emerging as a key evolutionary node. Positively selected sites identified in this study may represent mutation hotspots, providing potential targets for future cancer therapy research.